2016
DOI: 10.1182/blood-2015-12-687814
|View full text |Cite
|
Sign up to set email alerts
|

High-content screening identifies kinase inhibitors that overcome venetoclax resistance in activated CLL cells

Abstract: Key Points Patient-specific pathways of resistance to venetoclax can be identified by high-content screening of clinical samples with a KI library. Sunitinib may overcome resistance to venetoclax for many patients by downregulating the expression of Bcl-xl, Mcl-1, and A1 in CLL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 75 publications
2
95
0
Order By: Relevance
“…[70] In a high-content screening system that utilized an in vitro microenvironment model, the multi-kinase inhibitor sunitinib was identified as the clinically available kinase inhibitor most effective at overcoming venetoclax resistance (more than ibrutinib or idelalisib). [71] The mechanism was attributed to more efficient abrogation of microenvironment-mediated up-regulation of BCL-X L , MCL-1 and BFL-1/A1 by sunitinib. [71] Interleukin-4 (IL-4) signaling, which proceeds through the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway, has been identified as a resistance mechanism to BCR pathway inhibition in CLL,[72] and the dual SYK/JAK inhibitor, cerdulatinib inhibits BCR- and IL-4-induced downstream signaling in CLL cells and induces apoptosis, particularly in IGHV-unmutated samples (characterized by greater BCR-signaling capacity and response to IL-4), and also prevents anti-IgM- and nurse-like cell (NLC)-mediated production of the chemokines CCL3/CCL4.…”
Section: Major Determinants Of Venetoclax Resistance: Mcl-1 and Bcl-xlmentioning
confidence: 99%
See 1 more Smart Citation
“…[70] In a high-content screening system that utilized an in vitro microenvironment model, the multi-kinase inhibitor sunitinib was identified as the clinically available kinase inhibitor most effective at overcoming venetoclax resistance (more than ibrutinib or idelalisib). [71] The mechanism was attributed to more efficient abrogation of microenvironment-mediated up-regulation of BCL-X L , MCL-1 and BFL-1/A1 by sunitinib. [71] Interleukin-4 (IL-4) signaling, which proceeds through the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway, has been identified as a resistance mechanism to BCR pathway inhibition in CLL,[72] and the dual SYK/JAK inhibitor, cerdulatinib inhibits BCR- and IL-4-induced downstream signaling in CLL cells and induces apoptosis, particularly in IGHV-unmutated samples (characterized by greater BCR-signaling capacity and response to IL-4), and also prevents anti-IgM- and nurse-like cell (NLC)-mediated production of the chemokines CCL3/CCL4.…”
Section: Major Determinants Of Venetoclax Resistance: Mcl-1 and Bcl-xlmentioning
confidence: 99%
“…[71] The mechanism was attributed to more efficient abrogation of microenvironment-mediated up-regulation of BCL-X L , MCL-1 and BFL-1/A1 by sunitinib. [71] Interleukin-4 (IL-4) signaling, which proceeds through the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway, has been identified as a resistance mechanism to BCR pathway inhibition in CLL,[72] and the dual SYK/JAK inhibitor, cerdulatinib inhibits BCR- and IL-4-induced downstream signaling in CLL cells and induces apoptosis, particularly in IGHV-unmutated samples (characterized by greater BCR-signaling capacity and response to IL-4), and also prevents anti-IgM- and nurse-like cell (NLC)-mediated production of the chemokines CCL3/CCL4. [73] Cerdulatinib was able to overcome the protection afforded to CLL cells by anti-IgM, IL-4 or NLCs by preventing up-regulation of MCL-1- and BCL-X L , but did not affect BCL-2 levels.…”
Section: Major Determinants Of Venetoclax Resistance: Mcl-1 and Bcl-xlmentioning
confidence: 99%
“…CLL cells were purified from the blood of CLL patients and activated in lipid-poor conditions with IL2 and resiquimod to represent stimulatory signals in pseudofollicles (Oppermann et al, 2016). Addition of LDLs increased viable cell numbers, counted by trypan-blue exclusion, in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating CLL cells are readily obtained but studies of pseudofollicles require the use of in vitro models. We have found that much of the biology of pseudofollicles is captured by culturing circulating CLL cells with IL2, to represent T cell activity, along with the TLR7-agonist Resiquimod (Oppermann et al, 2016). The studies in this manuscript were designed to try to understand why hypercholesterolemia is apparently a tumor promoter for CLL by using this in vitro pseudofollicle model to observe how LDLs affect the biology of proliferating CLL cells.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that SYK inhibitors were the most effective of the agents tested with respect to downregulation of Mcl-1 and enhancement of venetoclax lethality [42]. Analogously, a high-content microscopic assay identified the multikinase inhibitor sunitinib as superior to BCR antagonists in potentiating venetoclax lethality in activated B cells [43]. …”
Section: Targeting Bcl-2 With Venetoclax In Hematologic Malignanciesmentioning
confidence: 99%